When basal cell carcinomas became giant: an Italian multicenter study. (27th November 2019) - Gualdi, Giulio; Monari, Paola; Calzavara‐Pinton, Piergiacomo; Caravello, Simone; Fantini, Fabrizio; Bornacina, Carlo; Specchio, Francesca; Argenziano, Giuseppe; Simonetti, Vito; Caccavale, Stefano; La Montagna, Maddalena; Cecchi, Roberto; et al.
Abstract: Background: Giant basal cell carcinoma (GBCC) is a basal cell carcinoma (BCC) enlarged in a diameter more than 5 cm. Since GBCCs are a highly infrequent entity and the occurrence rate is approximately 0.5–1% out of all BCC types, only anecdotal cases are reported, and causes and characteristics inducing development of this tumor are not defined. Objectives: Evaluate causative factors and clinico‐histological characteristics of GBCCs. Methods: The study is a 6‐month, hospital‐based case series study performed in 12 Italian dermatologic centers. Results: A total of 59 cases and 458 control BCCs were collected. No significant differences existed between the two groups if we take into account social or cultural factors. The average duration of GBCCs is considerably longer than controls. GBCCs are located on unexposed areas while BCCs are on areas not usually covered by clothes. Superficial histological subtype was more frequent in the BCCs group, while infiltrative in GBCCs. GBCCs showed significantly higher local invasiveness, and greater metastatic capacity. More than half of GBCCs had been previously treated with one or more treatments. Conclusions: Patients with GBCCs appear to belong to two categories: (i) those who present with GBCC due to delay in accessing medical attention, and (ii) those who have BCCs previously treated with inappropriate strategies. Only very few cases can be carried out with intrinsic biological features of tumor aggressiveness. Social and cultural conditions do not appear to be involved in the development of GBCCS. These observations may help clinicians in selecting correct therapeutic strategies in the treatment of BCCs, which give rise to GBCC.